2008
DOI: 10.25336/p6ww4j
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality in Nepal: Unraveling the Complexity

Abstract: Maternal mortality has been recognised as a public health problem in the developing countries. The situation concerning maternal mortality in Nepal remained unexplored and vague until the early 1990s. By using 1996 Nepal Family Health Survey, this study discusses the maternal mortality situation in Nepal and analyses the differentials in maternal mortality by place of residence, region, ethnic and religious groups, age at death, and parity. Almost 28 percent of deaths of women in reproductive age was accountab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Mothers that are too young are not physically ready yet to conceive and give birth. 7,8 Comparing the two highrisk age groups, more maternal deaths came from the young age mothers. 8 Mothers with a history of diseases had 19.828 times larger risk compared to those without any history.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers that are too young are not physically ready yet to conceive and give birth. 7,8 Comparing the two highrisk age groups, more maternal deaths came from the young age mothers. 8 Mothers with a history of diseases had 19.828 times larger risk compared to those without any history.…”
Section: Discussionmentioning
confidence: 99%
“…Out of nine, only three are organizational heads. As most of the respondents initially went to their local 23 South East Asia Journal of Public Health 2018;8(1): [22][23][24][25][26][27][28][29][30][31] Banik & Sumon  Barriers to access maternal health services doctors, who were basically drug peddlers and had minimum level of medical training, for treatment, this fact stimulated us for interviewing them.…”
Section: Development Of Research Instrumentmentioning
confidence: 99%
“…[5][6][7][8][9] One of the main reasons, as indicated by anecdotal evidence, for worse situation in maternal health (MH) is that women, particularly poor, have less access to healthcare services. In addition, a lot of research [10][11][12][13][14][15][16][17][18][19][20][21][22] found class and region-based inequity in access to primary, particularly maternal, healthcare services and broadly classified all access barriers into four sections; socio-cultural, financial, physical and organizational/ institutional. This research therefore intended to deal with the issue of maternal health care (MHC) services, provided by different organizations in Rajshahi City.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the Millennium Development Goals 4 and 5, Nepal has been lauded as a country that has had remarkable success. In the 20 years between 1996 and 2006, the MMR has been reduced from 539 per 100,000 to 281 per 100,000; under-5 child mortality has seen similar advances, from 118 per 1000 live births in 1996 to 54 per 1000 live births in 2011 [12,14]. 3 Programs such as the Aama Initiative, begun in 2007, have helped to subsidize (and, in some senses, incentivize) the cost of institutional deliveries.…”
mentioning
confidence: 98%